Does government health insurance reduce job lock and job push?. (1st May 2020) - Barkowski, Scott
Abstract: I study job lock and job push, twin phenomena believed to be partially due to employment‐contingent health insurance (ECHI). Using variation in Medicaid eligibility among household members of male workers to identify changes in those workers' reliance on ECHI, I estimate notable job lock and job push effects. For married male workers, a 15 percentage point increase in the likelihood a household member is eligible for Medicaid increases the rate of voluntary job exits over a four‐month period by 14%. For job push, the same increase in a household member's likelihood of Medicaid eligibility reduces the transition rate into jobs with ECHI among all male workers by 8%.